第一原理計算三元鹵化物結構穩定性與二階光學非線性係數頻率特性 - 張振雄; CHANG CHEN-SHIUNG (My University, 2008)
鈣鈦礦結構(Perovskite)之三元鹵化物( 3 CsGeX , X=Cl, Br, I)是新興的紅外線非線 性光學材料，它同時有鈣鈦礦晶體結構變異的有趣議題，也有優良的紅外線非線性光 學特性。跟以往採用贗勢法不同，本計劃以第一原理全勢計算方法進行系統化的分析 與探討。這包括了三種主要的晶體結構以及兩種次要晶相的聲子態計算；頻率相關二 階非線性光學係數( c (2) )的計算將與聲子態計算結果比較分析。同時也將與文獻以及 本實驗室過去粉末二倍頻量測(SHG)、光致發光量測(PL)、紅外線穿透光譜(FTIR)及拉 曼光譜量測結果與實驗數據作一比較。本計劃研究成果可提供晶體工程、晶體應用、晶 體物理特性等進一步的研究參考依據。

The perovskite ternary halides ( 3 CsGeX , X=Cl、Br, I) are noticed for nonlinear optical applications in infrared. Additionally, these ferroelectric (FE) materials display very peculiar structural, electrical, and electromechanical features. Unlike the previous first-principles pseudopotential mixed-basis method, we present a systematically investigation of the phonon spectrum from the of the first principle full-potential calculation method. While ferroelectric 3 CsGeX presents the cubic- rhombohedral phase sequence with decreasing T, their similar compounds KTaO3 and SrTiO3 are incipient ferroelectrics which exhibit the ferroelectric soft mode. Despite the large amount of research attracted by the above phenomenology since long ago, quite a few realistic model simulations are available. Many lattice dynamical calculations have been performed for each isolated material, but the only unified view of their ferroelectric behavior has been provided by the nonlinear halides polarizability model. Although initially based on phonon data for the cubic phase, recent first principles calculations confirm that the model is basically correct with regards to the energetics involved in the various ferroelectric distortions in 3 CsGeX . In this research, their calculated phonon spectrum, structural and nonlinear optical properties will be studied. They will also be compared with the powder second harmonic generation signals, the measurements of FTIR, the measurements of PL spectrum, raman spectrum in the previous studies. These properties will be addressed, by means of the first principles (ab initio) simulations, and will greatly expanded our understanding of this important class of materials.
First Priciples Studies of Structural Stabilities and the Frequency-Dependent Second Order Nonlinear Optical Susceptibilities in Ternary Halides
Keywords: 三元鹵化物; 第一原理計算; 二階非線性光學係數( c (2) ); 聲子; the first principle calculation; ternary halides; second order nonlinearoptical susceptibilities( c (2) ); phonon